2020
DOI: 10.1055/s-0040-1709524
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation via Shear Stress Exposure Induces a Differing Pattern of Biomarkers of Activation versus Biochemical Agonists

Abstract: Background Implantable cardiovascular therapeutic devices, while hemodynamically effective, remain limited by thrombosis. A driver of device-associated thrombosis is shear-mediated platelet activation (SMPA). Underlying mechanisms of SMPA, as well as useful biomarkers able to detect and discriminate mechanical versus biochemical platelet activation, are poorly defined. We hypothesized that SMPA induces a differing pattern of biomarkers compared with biochemical agonists. Methods Gel-filtered human pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 78 publications
0
53
0
Order By: Relevance
“…Externalization of anionic phospholipids on platelet surface, as a specific marker of shear-mediated platelet activation, 20 was examined using annexin V binding assay and quantified as MFI of annexin V–positive population. We showed that platelet annexin V binding gradually increased over the shear exposure time for both devices (Figure S2, Supplemental Digital Content, http://links.lww.com/ASAIO/A548 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Externalization of anionic phospholipids on platelet surface, as a specific marker of shear-mediated platelet activation, 20 was examined using annexin V binding assay and quantified as MFI of annexin V–positive population. We showed that platelet annexin V binding gradually increased over the shear exposure time for both devices (Figure S2, Supplemental Digital Content, http://links.lww.com/ASAIO/A548 ).…”
Section: Resultsmentioning
confidence: 99%
“… 37 , 38 Yet, we have previously shown that externalization of anionic phospholipids (as indicated by annexin V binding) is a characteristic signature of shear-mediated platelet activation as opposed to platelet activation by biochemical agonists, for example, ADP and thrombin. 20 Indeed, Mondal et al 39 , 40 reported that markers of platelet apoptosis and oxidative stress were elevated in bleeders versus non-bleeders among patient cohort supported by CF-VADs. However, we noted that annexin V binding was also elevated in the nonsheared control (see Figure S2, Supplemental Digital Content, http://links.lww.com/ASAIO/A548 , “240 Still” sample) suggesting that the shear-mediated increase of platelet annexin V binding observed in our study could be at least partially attributed to in vitro platelet “aging” occurring in blood samples during long-term storage and handling.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that IgGs from patients with severe COVID- (21). In contrast to PS, conventional markers of PLT activation were declared in this study to fail the detection of early activation events leading to thrombosis.…”
Section: Discussionmentioning
confidence: 55%
“…57 devices. 58 Albeit the anticoagulation properties of diverse sea cucumber species had already been identified, attempts had failed to isolate its oligosaccharides. Zhou et al 59 achieved this goal, allowing them to comprehensively characterize their individual structures in relation to biological activities.…”
Section: Novel Diagnostic and Therapeutic Targetsmentioning
confidence: 99%